O władzy ludzi nad zwierzętami w kulturze zachodniej – perspektywa posthumanistyczna - Gajewska, Grażyna (Studia Europaea Gnesnensia, 2015)
In this paper, I discuss the problem of human ascendance over animals. The issue is particularly important and often addressed in contemporary intellectual current referred to as posthumanism. In this framework, the interest in humanity is not abandoned, but one departs from the anthropocentric approach. The prefix “post” denotes a shift of focus, from problems and intellectual positions which underline the privileged status of the human to non-anthropocentric attitudes. These are non-anthropocentric humanities, although the designation itself is paradoxical, and undermines the legitimacy of the humanities in general, since anthropos is the principal subject of research of the discipline and the humanistic approach. For those reasons, “non-anthropocentric humanities” and other ones as well, such as “non-humanist anthropology”, “anthropology of objects”, “anthropology of cyborgs” or finally “posthumanities” provoke reservations. Still, this is a problem which always appears when appropriate words are lacking to describe a set of new tendencies, directions of research or intellectual approaches which have not yet developed a suitable terminology. The prefix “post” suggests that new phenomena cannot be rendered by means of the former notions and categories; new methods which make it possible have to be sought. In the case of notions such as “non-anthropocentric humanities” and “posthumanities”, the important thing is that they forecast as change of the dominant in the tendencies, directions and methods of (post)humanistic studies. They do not draw upon humanism as a specific approach to the world in whose centre one finds the human being, but to the non-essentialist and non-hierarchically oriented posthumanism.